The disruptive potential of digitalization and the current Swiss VET landscape - Kessler, Stefan [Verfasser]; Gonon, Philipp [Verfasser] (My University, 2021)
"Digitalization is regarded as having an extensive impact on the world of work and hence, affects vocational education and training (VET). This exploratory paper seeks to discuss the disruptive potential of digitalization in the current Swiss VET context on three levels: debates and concerns, politics and practices. Firstly, topical concerns regarding the future of work and the performance of VET as a training model are discussed. Secondly, the paper argues that the level of educational practice is a promising field of study in assessing the disruptive potential of digitalization, especially in dual training systems. The examples provided in this paper show that VET providers (both schools and firms) take different courses of action with respect to digitalization. They also demonstrate that the outcomes of digitalization for educational practice vary according to training needs and occupational requirements. Thirdly, digitalization emerges to a focal point in the present political agenda. Besides the promises and premises of a fundamentally changing VET landscape, digitalization primarily takes place as a gradual process of change." (Author's abstract ; BIBB-Doku)
Keywords: I 2.2.1 Westeuropa; S 1.3.1 Ausbildung im Dualen System; L 4.2.3 Internetbasiertes Lernen / E-Learning; 370; Schweiz; Duales System; Ausbildungsmodell; Digitalisierung; E-Learning; Lernen am Arbeitsplatz; Ausbildungsbetrieb; Berufsschule; Berufsbildungspolitik